Factors Affecting Return on Assets in IDX-Listed - Marwin Antonius Rejeki Silalahi; Siska Amonalisa Silalahi; Marwan Carlos Sahatdotua Silalahi (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2021)
This research begins with the plastic industry that is increasingly available on the Indonesia Stock Exchange, as seen by the increase in several plastic companies listed on the Indonesia Stock Exchange and the addition of foreign market share, namely Chinese products. This study aims to analyze the extent to which the performance development of plastic companies in Indonesia is seen from the Return on Assets as the dependent variable. While the independent variables of this study are Current Ratio, Total Asset Turnover, Debt Ratio, and Gross Profit Margin. The research method used in this study is a quantitative method, where this study has a sample of 207 data from 10 companies listed on the Indonesia Stock Exchange, with the period 2012 to 2019, and financial reporting is carried out during the quarter, where this study uses the normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, t-test, and F test. The results of this study are Current Ratio, and Total Asset Turnover has an effect on Return on Assets. On the other hand, the Debt Ratio and Gross Profit Margin variables have no effect on Return on Assets.